2016
DOI: 10.1111/anae.13640
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, cohort evaluation of major and minor airway management complications during routine anaesthetic care at an academic medical centre

Abstract: SummaryThe aim of this study was to develop an audit tool to identify prospectively all peri-operative adverse events during airway management in a cost-effective and reproducible way. All patients at VU University Medical Center who required general anaesthesia for elective and emergency surgical procedures were included during a period of 8 weeks. Daily questionnaires and interviews were taken from anaesthesia trainees and anaesthetic department staff members. A total of 2803 patients underwent general anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…Sore throat is common, important to patients and affects the quality of recovery . However, although there are some exceptions , much airway research does not assess sore throat even though complications are noted . Our systematic review suggests that corticosteroids applied to tracheal tubes were better than non‐analgesic controls and lidocaine for prevention of postoperative sore throat.…”
Section: Discussionmentioning
confidence: 87%
“…Sore throat is common, important to patients and affects the quality of recovery . However, although there are some exceptions , much airway research does not assess sore throat even though complications are noted . Our systematic review suggests that corticosteroids applied to tracheal tubes were better than non‐analgesic controls and lidocaine for prevention of postoperative sore throat.…”
Section: Discussionmentioning
confidence: 87%
“…In a prospective study, unanticipated difficulty in tracheal intubation occurred at a rate of 0.1% ; resolution of these difficulties was achieved with a videolaryngoscope in 52%, with fibreoptic intubation in 14% and with a combination technique in 10%. A Cochrane systematic review (64 RCTs, > 7000 patients, overall moderate quality evidence) reported numerous benefits of videolaryngoscopy vs. direct laryngoscopy for tracheal intubation .…”
Section: Avoiding Failed Tracheal Intubation and Its Sequalaementioning
confidence: 99%
“…Huitink et al. adopted a different approach, and attempted to capture all potential and actual significant airway events in a Dutch University hospital's operating theatre over a 60‐day period . Cases were identified by daily interviews with clinicians, being volunteered by clinicians and by triggered interviews when the anaesthesia information system detected an episode of oxygen desaturation (SpO 2 < 93%).…”
Section: Epidemiology Of Major and Minor Airway Eventsmentioning
confidence: 99%
“…In these cases, awake nasal fibreoptic intubation is still essential. However, awake videolaryngoscopy would be entirely appropriate in patients who were difficult to mask ventilate and in the obese, as complications are frequent in those with a higher body mass index . Indeed, one of the studies included in Alhomary et al.…”
Section: Making a Choicementioning
confidence: 99%